2021
DOI: 10.1111/prd.12383
|View full text |Cite
|
Sign up to set email alerts
|

Treatment planning considerations in the older adult with periodontal disease

Abstract: Periodontal health in the elderly is influenced by numerous factors, including systemic conditions, patient compliance, age‐associated changes, and restorative procedures. The numerous comorbidities seen in the elderly necessitate individualized approaches for treatment planning. In this paper, we review how age, comorbidities, oral hygiene, and restorative dental procedures collectively influence the treatment and management of the periodontium in the elderly. The elderly population is predicted to double in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 101 publications
1
17
0
2
Order By: Relevance
“…The oral healthcare giver has to take into consideration any other coexisting pathologies-other health issues such as xerostomia, presence of dental plaque, caries, prosthetics and also systemic diseases that could lead to altered wound healing and altered bone physiology and could influence the treatment and the prognosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The oral healthcare giver has to take into consideration any other coexisting pathologies-other health issues such as xerostomia, presence of dental plaque, caries, prosthetics and also systemic diseases that could lead to altered wound healing and altered bone physiology and could influence the treatment and the prognosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resin‐based composites are nowadays commonly applied as permanent filling materials. However, their use also encompasses use as temporary dental restoration materials (e.g., temporary crowns and bridges), which in the same way as subgingival composite restorations may be in close contact with the gingival tissue, which may be inflamed [7, 8]. In this context, several scientific studies investigated the provision of dental restorative materials with antimicrobial ingredients usually used in dental prophylaxis like octinidine (di)hydrochloride (ODH) or chlorhexidine diacetate (CHX).…”
Section: Introductionmentioning
confidence: 99%
“…Some other studies have also shown that smoking is one of the important factors affecting bone loss around implants. [19] In related studies, smoking patients with periodontal disease have significantly lower repair success rate than non-smoking patients, and the probability of peri-implant inflammation is about 80-85% and 20-30% respectively. (3) Diabetes: another important risk factor for periodontal disease is diabetes mellitus.…”
Section: Factors Affecting the Prognosis Of Implant In Patients With ...mentioning
confidence: 99%